Death to the Cobb-Douglas production function - Sebastian Gechert; Tomas Havranek; Zuzana Irsova; Dominika Kolcunova (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2019)
We show that the large elasticity of substitution between capital and labor estimated in the literature on average, 0.9, can be explained by three factors: publication bias, use of aggregated data, and omission of the first-order condition for capital. The mean elasticity conditional on the absence of publication bias, disaggregated data, and inclusion of information from the first-order condition for capital is 0.3. To obtain this result, we collect 3,186 estimates of the elasticity reported in 121 studies, codify 71 variables that reflect the context in which researchers produce their estimates, and address model uncertainty by Bayesian and frequentist model averaging. We employ nonlinear techniques to correct for publication bias, which is responsible for at least half of the overall reduction in the mean elasticity from 0.9 to 0.3. The weight of evidence accumulated in the empirical literature emphatically rejects the Cobb-Douglas specification.
Keywords: D24; E23; O14; 330; Elasticity of substitution; capital; labor; publication bias; model uncertainty